Aurelian and the third century - Watson, Alaric, 1958- (Roman imperial biographies., 1999)
Aurelian and the Third Century provides a re-evaluation in the light of recent scholarship of the difficulties facing the Roman empire in the AD 260s and 270s, concentrating upon the reign of emperor Aurelian and his part in surmounting them.